Scoping review of current challenges and circumstances impacting Indigenous applications to Canadian medical schools - Kliska, Elizabeth; MacLean, Andrew; Farrugia, Patricia (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2024)
Introduction: Considering the relevant 2015 Truth and Reconciliation Commission recommendations, this paper reviews the current state of Canadian medical schools’ Indigenous admissions processes and explores continued barriers faced by Indigenous applicants.Methods: A summary of literature illustrating disadvantages for Indigenous applicants of current admissions tools is presented. A grey literature search of current admissions requirements, interview processes, and other relevant data from each medical school was performed. Tables comparing differences in their approaches are included. A calculation of Indigenous access to medical school seats compared to the broader Canadian population was conducted. Gaps in execution are explored, culminating in a table of recommendations.Results: Despite formal commitments to reduce barriers, Indigenous applicants to medical school in Canada still face barriers that non-Indigenous applicants do not. Most programs use tools for admission known to disadvantage Indigenous applicants. Indigenous applicants do not have equitable access to medical school seats. Facilitated Indigenous stream processes first ensure Indigenous applicants meet all minimum requirements of Canadian students, and then require further work.Discussion: Seven years after the Truth and Reconciliation Commission called on Canadian universities and governments to train more Indigenous health care providers, there has been limited progress to reduce the structural disadvantages Indigenous students face when applying to medical school. Based on best practices observed in Canada and coupled with relevant Indigenous-focused literature, recommendations are made for multiple stakeholders.Conclusions: The study was limited by the data available on numbers of Indigenous applicants and matriculants. Where available, data are not encouraging as to equitable access to medical school for Indigenous populations in Canada. These findings were presented at the International Congress of Academic Medicine 2023 Conference, April 2023, Quebec City, Canada.